The premium for organic wines: Estimating a hedonic price equation from the producer side - Alessandro Corsi; Steinar Strøm (University of Oslo, Department of Economics, 2009)
Organic production techniques are an increasing, though minor so far, part of agriculture, and organic wines are increasingly produced and appreciated. Nevertheless, since the organic technique is more costly, a crucial question is whether organic wines benefit from a price premium. In this paper a hedonic price function has been estimated for Piedmont organic and conventional wines. Unlike the current literature on the determinants of wine prices, we used data on the production side in addition to variables of interest for consumers. One question was whether farm and operator's characteristics of no interest for consumers affect wine prices. The second question was whether organic wine obtains a price premium relative to conventional wine. Our results show that, along with characteristics that are of interest to consumers, like the appellation and the variety, some farm and producer characteristics that are not directly relevant for consumers do significantly affect wine prices. We also find that, though there is not a premium in the sense of an addition to other price components, given farmers' and wines' characteristics, organic wines do command higher prices.
Keywords: C21; L11; Q12; 330; Organic wine; hedonic price; price premium; Piedmont; Wein; Biokost; Ökologischer Landbau; Hedonischer Preisindex; Preisdifferenzierung; Piemont; Italien